Living with the enemy : inside North Korea - Saccone, Richard (Hollym International Corp., 2006)
Describes the author's travel experiences and cultural observations while working for the Korean Peninsula Energy Development Organization (KEDO) as a U.S. representative to build a nuclear power plant for the North Koreans. After living there on and off for almost fourteen years, Saccone seeks "to recognize Inaccurate portrayals of North Korea and reveal the truth."